2020
DOI: 10.1038/s41598-020-62731-3
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life analysis in differentiated thyroid carcinoma patients after thyroidectomy

Abstract: Although differentiated thyroid carcinoma (DTC) has a good prognosis and survival rate, long-term medication and recurrence monitoring might be needed. The factors that affect postoperative healthrelated quality of life (HRQoL) in patients with DTC in different regions remain unclear or conflicting. The purpose of this study was to assess the factors that influence the HRQoL of DTC patients after surgery. This study selected 174 patients with DTC who underwent thyroidectomy. Additionally, 174 participants who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…In a retrospective study, Nickel et al 27 reported that the immediate postoperative QoL was better after HT than after TT in patients treated for DTC. Li et al 28 compared HRQoL at 1 year, using the SF‐36 questionnaire, between patients treated with thyroidectomy and a control group. They concluded that the major determinants of HRQoL deterioration after thyroidectomy were diabetes mellitus, hypertension and depression.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, Nickel et al 27 reported that the immediate postoperative QoL was better after HT than after TT in patients treated for DTC. Li et al 28 compared HRQoL at 1 year, using the SF‐36 questionnaire, between patients treated with thyroidectomy and a control group. They concluded that the major determinants of HRQoL deterioration after thyroidectomy were diabetes mellitus, hypertension and depression.…”
Section: Discussionmentioning
confidence: 99%
“…The QOL of DTC patients was evaluated at one year of follow-up. DTC patients showed much lower scores on different domains except for physical functioning, which was measured using the SF-36 questionnaire [13].…”
Section: Discussionmentioning
confidence: 99%
“…Voice alteration, swallowing dysfunction, pain, fatigue, appearance of scar, and concern about weight gain are several thyroid-specific quality of life (QOL) issues identified by previous studies [10][11][12][13][14]. Moreover, some patients struggle to cope with and adapt to the lifelong thyroid hormone replacement postthyroidectomy [15].…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published randomized controlled trial, QoL significantly increased after surgery in a cohort with euthyreotic Hashimoto's disease compared to a cohort only receiving hormone substitution alone [45]. Altogether, QoL data in thyroid surgery are sparse to find in literature and in the available data most patients perform worse in different aspects of QoL with thyroid disease and even after thyroid surgery for years in benign or malign disease [43,44,[46][47][48]. Therefore, the decrease especially in physical health composite scale, may not be due to the surgery itself.…”
Section: Discussionmentioning
confidence: 99%
“…Remote access endoscopic thyroid surgery like EndoCATS and ABBA procedures can be safely performed with an excellent cosmetic outcome and highly satisfied patients. The QoL in these patients is impaired, but presumably independent of surgery or surgical technique [ 43 , 44 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%